Education as a Process of Humanization: A Philosophical and Scientific Examination of the Development of the Whole Human Being - Atika Zikri; Amril Amir; Nurizzati Nurizzati (Jurnal Syntax Transformation, 2026)
The reduction of education to a technocratic process that is only oriented towards cognitive achievement has ignored basic human values. This research aims to analyze the essence of education as a humanization process by integrating philosophical and scientific perspectives, as well as identifying the main dimensions in the development of the whole human being. The method used was a systematic literature review of 28 articles from Scopus, Web of Science, and the Garuda Portal for the 2014–2024 period with the keywords "humanization in education", "philosophy of education", and "holistic development". The thematic analysis yielded three main findings. First, the humanization of education includes five dimensions of development: cognitive, affective, moral, social, and spiritual, that must be integrated into learning practices. Second, the philosophy of education serves as a normative foundation and a tool of criticism that directs educational goals. Third, education provides an empirical framework through theoretical, practical, and normative orientations. These findings confirm that meaningful education requires a dialogue between philosophical reflection and scientific validation in its implementation. This research contributes to educational theory by providing an integrated conceptual framework that bridges the gap between philosophical ideals and empirical practice, offering practical guidance for educators and policymakers to develop more humanistic and holistic educational systems that address the ethical and social challenges of contemporary society.